Temas contemporâneos e transversais na BNCC: as contribuições da transdisciplinaridade - Cordeiro, Natália de Vasconcelos (2019)
National education, specifically the teaching and learning process, underwent a relevant change and reflection, due to the approval of the National Curricular Common Base (BNCC) in December 2017 that, in addition to relating skills considered essential for all students of Basic Education, according to the content of their texts, also concerned with the training promote a comprehensive education and with full development of students. In this sense, themes that are not exclusive to curricular components, but that affect society and human life, were incorporated by BNCC with a transversal and integrative approach. However, the BNCC did not expand non-disciplinary issues and a transversal approach, so it is common that there are doubts and questions about the subject, for example: how to articulate the themes with the other contents? How to work the topics in a contextualized way and within the curricular components? From this perspective, it is understood that a transdisciplinary approach of these subjects can contribute to the treatment of these subjects in the school, since transdisciplinarity, in general lines, seeks to give a new look to the knowledge, in which the barriers break, opening for the articulation and relationship between them. Thus, a research topic that deserves to be highlighted is the contribution of transdisciplinarity to addressing the Transversal Themes (and contemporaries) of the BNCC. The present research does not only seek to understand the contemporary themes of transversal approach, but also to discuss the possibilities of applying transdisciplinarity in the treatment of contemporary themes of BNCC, being this the general objective of the research. Therefore, the problem revolves around the following question: how is transdisciplinarity a possible approach to contemporary BNCC issues? It is hoped that this research may represent a contribution to those who believe that education in its complexity is a decisive factor for the construction of a more democratic, ethical and human society that respects and values? in all aspects (cultural, social and historical), the social groups that compose it. In addition, through analysis and research on Transversal Themes (and contemporaries), we seek to make them more known, realizing that all educators and other members of society are, in a way, responsible for their implementation and supervision.